Semantic web evaluation challenge : SemWebEval 2014 at ESWC 2014, Anissaras, Crete, Greece, May 25-29, 2014, Revised selected papers - SemWebEval (2014 : Crete, Greece).; Presutti, Valentina; Stankovic, Milan; Cambria, Erik; Cantador, Ivan; Ohio Library and Information Network; Extended Semantic Web Conference 2014 : Crete, Greece) (Cham : Springer, 2014)
This book constitutes the thoroughly refereed post conference proceedings of the first edition of the Semantic Web Evaluation Challenge, SemWebEval 2014, co-located with the 11th Extended Semantic Web conference, held in Anissaras, Crete, Greece, in May 2014. This book includes the descriptions of all methods and tools that competed at SemWebEval 2014, together with a detailed description of the tasks, evaluation procedures and datasets. The contributions are grouped in three areas: semantic publishing (sempub), concept-level sentiment analysis (ssa), and linked-data enabled recommender systems (recsys)
Includes index.
Keywords: Semantic Web -- Congresses; Computer science